Physical encounters impose a consistency–amount trade-off on bacterial group formation in marine environments - Thomas C. Day; Julia A. Schwartzman (Proceedings of the National Academy of Sciences, 2026)
Physically associated bacterial groups can enhance resilience through emergent traits, including access to inaccessible substrates, increased stress tolerance, and reduced predation. These traits arise from physical and chemical interactions between cells and constitute multicellular behavior, yet we lack general principles predicting when this form of multicellularity provides ecological advantages. Here, we examine how the size of bacterial groups influence encounters with two particle types: resources and lytic bacteriophage. Using a size-dependent encounter theory, we identify regimes where encounter rates depend on group size. Experiments with the group-forming marine bacterium Vibrio splendidus 12B01 confirm that larger groups encounter particles more frequently. However, increasing group size reduces both the mean and variance of particle encounters per cell, revealing a trade-off between the consistency and amount of resource encountered. Stochastic simulations support this trade-off and predict conditions under which consistent encounters with resource particles benefit groups more than single cells, and where multicellular behaviors can alleviate resource limitation within groups. Simulations of encounters with phage-like particles predict that consistent encounters can stabilize the average time to infection for individual cells—the livable timescale—by disrupting viral replication and burst feedback. Overall, our results suggest that bacterial group formation can support resource acquisition despite predation. We predict that this advantage emerges in fluctuating fluid environments and is constrained by size- and concentration-dependent encounter physics. More broadly, these findings identify a simple physical mechanism through which multicellular groups may provide ecological advantages across diverse microbial systems.